Campaigning for public awareness on cycling. - (:unkn) unknown (Deutsches Institut für Urbanistik (Difu), 2012)
In Germany experience shows that cycling campaigns have become vital and cost-effective instruments to promote cycling. Especially when they enjoy political backing, communication activities can be conducive to higher cycling levels and better valorise cycling infrastructure. (Difu)
Keywords: Radverkehrskampagne; Kampagne; Good Practice; Individualverkehr; Fahrradverkehr; Kommunikation; Öffentlichkeitsarbeit